Acute muscle adaptations to a resistance exercise - Yang, Y.; Chaves, E.; McCrory, J. L. (ISB Congress, 2005)
The purpose of this study is to examine neural adaptations resulting from a single-session of resistance exercise training. It was hypothesized that the neural adaptations will be observed following a single session of resistance exercise training.